A highly sensitive "turn‐on" fluorescent sensor for the detection of human serum proteins based on the size exclusion of the polyacrylamide gel. Issue 4 (February 2014) - Xu, Shenghao; Liu, Pingping; Lu, Xin; Zhang, Jing; Huang, Lingyun; Hua, Wenhao; He, Dacheng; Ouyang, Jin
<x xml:space="preserve">Abstract</x> Electrophoresis 2014, 35, 546‐553. DOI: 10.1002/elps.201300308 Polyacrylamide gel, with a porous three dimensional network structure of nanoscale, is an excellent material for protein separation. Each protein could be fixed in the gel to form bands after separation. Here, we use inhomogenous colloidal silver nanoparticles as the staining reagent for detection of the proteins. Owing to the different aperture and size exclusion effect of the polyacrylamide gel, silver nanoparticles of less than 5 nm in diameter could interact with the proteins inside the gel, generating red fluorescence. A highly sensitive "turn‐on" fluorescent sensor based on the size exclusion effect of the polyacrylamide gel was therefore developed for the on‐gels protein detection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>